RESPON PEKERJA SEKTOR INFORMAL TERHADAP PELAKSANAAN PROGRAM ASURANSI KESEJAHTERAAN SOSIAL KELURAHAN POLONIA KECAMATAN MEDAN POLONIA - T.MELVIRA Novita Sari (Welfare StatE, 2013)
In the crisis situation that allows for changes in the condition of the main breadwinner in the family either because of illness , accident , death , then Askesos is one of the social welfare system that is able to provide assistance or protection against tersebut.Masalah conditions are discussed in this study is How Response Workers Against the Informal sector Social Welfare Insurance Program in the Village Polonia Medan Polonia District . Which is the goal of this research was to determine the response of the informal sector workers against insurance social welfare program in the Village Polonia Medan Polonia District . Through this research is expected to develop concepts and theories relating to social security and social welfare insurance . The research was conducted in the Village polonia Medan Polonia District . This study considered descriptive type with total population of 169 souls who then took a sample of 69 people. Sampling was conducted using stratified random sampling technique . To obtain the data , researchers used data collection techniques library research and field study using questionnaires and interview research instruments . In analyzing the data , researchers used quantitative analysis methods with descriptive data analysis . Based on the results of the data analysis it can be concluded that the informal sector workers in the Village Polonia agree with the implementation of the Social Welfare Insurance program launched by the government in cooperation with the Institute YAKMI . Their stated reason is because they were helped when they can not earn a living due to illness , accident or death . In addition they also become accustomed to saving money every month . Keywords : informal workers, social security